Trace metal profile of some fruits in Kokori and Abraka Market, Delta State, Nigeria - O.M., Agbogidi (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
An investigation was carried out in Abraka and Kokori communities of Delta State, Nigeria in 2013 to evaluate the trace metal concentration in some fruits: pawpaw, banana, orange and African garden egg commonly grown and sold in their market with a view to establishing baseline information on their trace metal elements. The fruit tissues were ashed, wet-digested and analyzed using atomic absorption spectrophotometer following the additive method. The results indicated the presence of elevated trace elements including lead, chromium, cadmium, zinc, manganese, nickel, cobalt and copper in the test fruits from Kokori market when compared with values obtained from the same fruits obtained from Abraka (a non oil producing community) in the same local government. The results also showed a highly significant (P<0.05) difference relative to the control (Abraka) values. Though, the values of the trace metals obtained fell below the critical permissible level following FAO and FEPA and WHO standards, their persistence in soil due to their non-biodegradability raises environmental concern because of the inter dependence between plants and animals including man in the ecosystem. The need for metal monitoring in food materials including fruits most available, affordable and sustainable sources of micronutrients in diets should be encouraged. Finding from this study have practical application in environmental science, health management and crop improvement.